The effect of fraction composition and protectants on sowing characteristics of spring barley seeds - Yu. G. Skvortsova; G. A. Filenko; T. I. Firsova; E. G. Filippov (Зерновое хозяйство России, 2018)
The effect of fraction composition and protectants on sowing characteristics of spring barley seeds The use of optimal seed fractions for sowing is an important agrotechnical technique for increasing the yield of spring barley. At present, investigations are under way to study the different grain sizes of spring barley seeds for sowing. The article presents the results of studies conducted in 2016-2017, to determine the effect of various disinfectants on the sowing characteristics of spring barley seeds, depending on the fractional composition. In laboratory tests, it was found that the treatment of barley seeds with various preservatives, depending on the fractional composition, influenced the planting qualities and stimulated growth processes. Thus, in the fractions isolated on sieves with aperture diameter (2.4 * 20mm and 2.6 * 20) using Lamador, KS and Ranazol Ultra, KC, the highest germination energy (from 84 to 89%) and laboratory germination (from 95 up to 97%). For most values of the intensity of growth of shoots, the optimal variants of the experiment were established on fractions 2,4 * 20 and 2,6 * 20 when treated with Ranazol Ultra, CS. On the control (without treatment), the maximum length of the germ on the fractions (2.0 * 20 and 2.2 * 20) was also noted and was 12.5 and 14.0 cm. The length of the sprout in the fraction (2.2 * 20) in the control and seed treatment with Ranazol Ultra, KS was almost identical. The highest yield was obtained with the use of the average fraction of seeds (2,4 * 20), with preplant seed treatment with Ranazol Ultra, KS - 10.2 t / ha; the smallest when treated with Vitovax 200 FF, VSC (8.6 t / ha). The data obtained make it possible to recommend the use of seeds with a fraction composition of 2,4 * 20 in combination with presowing treatment with Ranazol Ultra disinfectant, KS to obtain better seed and high yield of spring barley.